A Study on Poetry of Philip Larkin: Exploring the Poetry and Legacy of Philip Larkin (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Norman Heffares, a modern literary critic has commented, “Philip Larkin’s greatness issecure. Nearly half a century later, the same can be said with perhaps even greater force”. Obviously, Norman Heffares intends to emphasize. Larkin’s convincing stature as a poet and that his achievement remains unfaded even now. L arkin has earned his place among the century's most illustrious and illustrious poets. As a result, this article examines Philip Larkin's poetry, interviews, and private writing to develop the theoretical framework of the poetry.